Hedonic and utilitarian purchases and construal level theory in the perception of justice and price fairness: behavioral and physiological perspectives - Isabella, Giuliana (2015)
Consumers make purchasing decisions every day. Among their purchases, consumers shop for hedonic and utilitarian products. In general, hedonic consumption is related to fun, pleasure, excitement, fantasy, experimental situations, or sensual pleasure. On the other hand, utilitarian consumption is related to instrumental and functional needs or products. Studies in psychology have shown that the information processes used to understand words and pictures are different. Since marketing researchers employ both types of stimuli, it is necessary to test how different stimuli can influence consumer behavior. Therefore, this study verified the influence of hedonic and utilitarian purchases and presentation types (pictures versus words) on consumers\' perceptions of justice and price fairness based on anger as a mediators and construal level theory. Because discriminatory pricing is a widely employed market practice, it was used the price changing (increasing or decreasing) contexts in the studies to manipulate perception of justice and price fairness. Based on that, ten hypotheses were developed and divided into sub items, which were tested with behavioral or physiological studies. The physiological data were collected by an electrocardiogram, electrodermal, and electromyography. The data analyses were done with analyses of variance (ANOVA), analyses of covariance (ANCOVA), and generalized estimation equations (GEE). The main result was that in picture presentations (low construal level), when consumers pay more than others to purchase utilitarian products, they perceive the situation as less just and more price unfairness compared to when the product is hedonic. In a word presentation (high construal level), the perceptions of justice, price fairness, perception of value, and the intention to repurchase are lower with the presentation of utilitarian products compared to hedonic products. In terms of physiological analyses, attention, arousal, and valence were tested to compare the product and presentation types. This study is relevant to marketing theory, as many academics utilize words and pictures as stimuli, but few address the differences due to representation types. By studying different products, such as hedonic and utilitarian, and using consumers\' affective and rational properties, it was found that the anger evoked in consumers by products are mediators in price fairness perception. This dissertation also contributes to understanding product evaluations in post-purchase situations, as opposed to during the choice process, which is found in the literature most often. For practitioners, this study makes important contributions by showing that the way a product is exposed (with words or pictures) influences the perception of justice when consumers realize that discriminatory pricing is being practiced.